Ruptured Right Ovarian Dermoid Cyst in a Multiparous Woman: A Case Report - Gurung, Saraswati; Lama, Jyoti Bhaju; Neupane, Sujata Khadka; Shrestha, Salina (Medical Journal of Eastern Nepal, 2024)
Ovarian dermoid cysts, or mature teratomas, rarely present with complications such as rupture. We report a case of a ruptured right ovarian dermoid cyst in a multiparous woman, emphasizing the importance of timely diagnosis and management. A 31-year-old woman presented with acute lower abdominal pain and vomiting. Ultrasonography indicated bilateral dermoid cysts, with rupture on the right side, leading to emergency right-sided salpingo-oophorectomy and left-sided ovarian cystectomy. The postoperative course was uneventful, and histopathology confirmed benign cystic teratomas in both ovaries. This case underscores the need for a multidisciplinary approach in managing such uncommon conditions.